(untitled) (Repertorio Científico, 2022)
Introduction: Objective: Analyze handling, storage and disposal of mercury during gold extraction process in Small-Scale Artisanal Gold Mining mill sites, to determine environment and the miners health risks. Methods: in June 2021, 10 mill sites were observed using checklists, and 15 coligalleros were interviewed, a guide to analyze risks to health and the environment was used based on “Methodology for risks and dangers evaluation in gold mining”. Results: According to Decree 37225-MINAET 59.26% of the mill sites compliance with physical-sanitary conditions, 87% of the coligalleros indicated that they have not received training on mercury management. Environment and miners health hazards due to exposure to mercury were observed in all mill sites. Environmental risk were classified between low and moderate, most important ones occur during grinding process because mercury is handled in mill sites that do not have ventilation system with localized extraction installation (chapel), and because mercury is stored in places where temperature is not regulated to be below mercury vaporization point (20 °C). Health risks for the coligalleros were classiffied between low, moderate and medium, most important risks occur when storing or handling mercury in mill sites without using personal protective equipment such as appropriate respiratory masks. Conclusion: Mercury use in Small-Scale Artisanal Gold Mining produces environmental and miners health risks , being grinding the stage process with the greatest exposure. However, the miners (coligalleros) are unaware of preventing and mitigating measures when handling, storing and disposing mercury in mill sites. Consequently, State advice and support is required to implement technologies that allow mercury reconverting and mercury amount reduction, in accordance with Minamata Convention.